Synergistic antibacterial effect of statins with the complex {[1-(4-bromophenyl)-3-phenyltriazene N 3 -oxide-κ 2 N 1 ,O 4 ](dimethylbenzylamine-κ 2 C 1 ,N 4 )palladium(II)} - Roberta Filipini Rampelotto; Vinicius Victor Lorenzoni; Danielly da Costa Silva; Guilherme A. de Moraes; Marissa Bolson Serafin; Maísa Kräulish Tizotti; Silvana Coelho; Priscilla Zambiazi; Manfredo Hörner; Rosmari Hörner (Universidade de São Paulo, 2018)
Abstract The treatment of infections caused by resistant microorganisms represents a big challenge in healthcare due to limited treatment options. For this reason, the discovery of new active substances which are able to perform innovative and selective actions is of great impact nowadays. Statins and triazenes (TZC) have consolidated as a promising class of compounds, characterized by the expressive biological activity, especially antimicrobial activities. The aim of this study was to assess the in vitro synergistic antibacterial effect of the association of statins and a new TZC complex {[1-(4-bromophenyl)-3-phenyltriazene N 3-oxide-κ 2 N 1,O 4](dimethylbenzylamine-κ 2 C 1,N 4)palladium(II)} (Pd(DMBA)LBr) against American Type Culture Collection (ATCC) strains and clinical isolates. The complex and the statins showed bacterial activity of all tested strains and clinical isolates, evidencing that TZC complexion with metals can be promising. Simvastatin showed synergy when associated to the complex (FICI≤0.5), being the minimum inhibitory concentration (MIC) of 16 µg mL-1 found in 6 samples. Thus, it is possible to infer that the association between Pd(DMBA)LBr and simvastatin consists of an alternative to increase the pontential of these compounds, since statins have low toxicity.